Effect of soy protein on hypercholesterolemia and hypertension to reduce the risk of cardiovascular diseases: Effect of soy protein on hypercholesterolemia and hypertension - Zahid, Saman; Zahoor, Tahir; Nadeem, Muhammad; Jahangir Chughtai, Muhammad Farhan; Khaliq, Adnan; Ahsan, Samree; Sagheer, Ambreen (Progress in Nutrition, 2020)
High blood cholesterol and hypertension are the leading causes of cardiovascular diseases which are one of the leading causes of death worldwide. The current research study was designed to isolate soy protein to be used as nutraceutical agents against hypercholesterolemia and hypertension. Soy protein was extracted and isolate was given to rats for 4 weeks after inducing hypercholesterolemic and hypertensive conditions. Blood samples were collected and analyzed for lipid profile (cholesterol, triglycerides, low density lipoprotein and high density lipoprotein) and serum nitric oxide on 14th and 42nd days of study. The results revealed significant decrease in total cholesterol (120.00 to 110.00 ml/dL), triglycerides (87.66 to 74.00 mg/dL), and low density lipoprotein (67.00 to 47.66 mg/dL) while significant increase in high density lipoprotein (29.33 to 50.00 mg/dL) and nitric oxide (24.00 to 50.33 mg/dL) due to the uptake of soy protein isolate for a period of 28 days was observed.